Eliminating Stubborn Insulated Deposition by Coordination Effect to Boost Zn Electrode Reversibility in Aqueous Electrolyte - Jiang, Yuzhuo; Xia, Xinyao; Qian, Siyi; Zhang, Jing; Zhou, Pinxin; Gu, Xuefang; Tian, Shu; Qian, Yijun; Ji, Haoqing; Liu, Jie; Qian, Tao (Frontiers in Chemistry, 2022)
Aqueous rechargeable zinc-ion batteries (ZIBs) have recently shined in energy storage and transmission, which are due to high safety and low cost. However, the extremely stubborn by-products in the Zn anode severely inhibited the Zn2+ adsorption/desorption and exacerbated the dendrite formation. Herein, we report a facile strategy to eliminate inert Zn4(OH)6SO4•xH2O for the improvement of ZIBs according to coordination effect by employing ethylenediaminetetraacetic acid-diamine (EDTA-2Na) as coordination additive in traditional electrolyte. Zn2+ is coordinated with the carboxyl group of the four acetyl carboxyl groups and the N in C-N bonds, forming a new chelating structure, and thus stubborn deposition will be dissolved in the electrolyte. As a result, the discharge capacity of 102 mAh g-1 in the ZnSO4/Li2SO4 with EDTA-2Na electrolyte at a current density of 4 C and a stable cycle life with capacity of 90.3% after 150 cycles are achieved. It has been concluded that the coordination effect strategy provides a valuable idea for solving the defects of ZIBs.